2017
DOI: 10.1002/gps.4770
|View full text |Cite
|
Sign up to set email alerts
|

Does baseline depression increase the risk of unexplained and accidental falls in a cohort of community‐dwelling older people? Data from The Irish Longitudinal Study on Ageing (TILDA)

Abstract: The risk of falls associated with depression in older adults is more marked for UFs, with the association for AFs approaching borderline significance only. This finding is important because UFs require focused clinical assessment with attention to potential causes such as cardiac arrhythmia or orthostatic hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 46 publications
(61 reference statements)
4
33
0
1
Order By: Relevance
“…43 Prior studies have also identified an association between other conditions potentially caused by low BP and deficits in cerebral perfusion, including stoke, syncope, and unexplained falls. [44][45][46] aOH-30 did not predict depression. There were no significant differences between those with sOH-30 and aOH-30 in terms of age, sex, cardiovascular disease, or use of culprit medications.…”
Section: Discussionmentioning
confidence: 76%
“…43 Prior studies have also identified an association between other conditions potentially caused by low BP and deficits in cerebral perfusion, including stoke, syncope, and unexplained falls. [44][45][46] aOH-30 did not predict depression. There were no significant differences between those with sOH-30 and aOH-30 in terms of age, sex, cardiovascular disease, or use of culprit medications.…”
Section: Discussionmentioning
confidence: 76%
“…It should be noted that depressive symptoms and fall are both dynamic and under progressive processes. Previous studies indicated that fall can result in depressive symptoms, and in turn, depressive symptoms can lead to fall accidents, which can further cause many health problems [1114]. Previous literature have studied the association between baseline depressive symptoms and subsequent fall accidents [1115] in other populations; however, the research relating to the association between depressive symptoms and subsequent fall accidents for Chinese people aged 45 and over is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that fall can result in depressive symptoms, and in turn, depressive symptoms can lead to fall accidents, which can further cause many health problems [1114]. Previous literature have studied the association between baseline depressive symptoms and subsequent fall accidents [1115] in other populations; however, the research relating to the association between depressive symptoms and subsequent fall accidents for Chinese people aged 45 and over is lacking. Since 30% of men and 43% of women in China were suffering from depressive symptoms [16], it is urgent and meaningful to investigate the association between depressive symptoms and fall accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Late‐life depression is associated with an increased risk of falls, which may be related to gait disturbance . Importantly, cerebral white matter disease has also been shown to predict incidence of depression in later life, as well as poorer prognosis …”
mentioning
confidence: 99%
“…12 Late-life depression is associated with an increased risk of falls, which may be related to gait disturbance. 13 Importantly, cerebral white matter disease has also been shown to predict incidence of depression in later life, as well as poorer prognosis. 14 To date, most work examining gait patterns in late-life depression is cross-sectional and longitudinal studies have not yet examined the role of specific gait characteristics as markers of risk.…”
mentioning
confidence: 99%